Stromelysin and tissue inhibitor of metalloproteinases gene expression in rheumatoid arthritis synovium. - Firestein, G. S. (1992)
In situ hybridization was used to localize stromelysin mRNA in rheumatoid arthritis synovial tissue. Stromelysin antisense probes hybridized primarily to the intimal lining layer in frozen tissue sections, with little or no sublining signal. The expression of stromelysin correlated with cellularity as determined by hybridization with an actin probe. Double-label experiments were performed to detect tissue inhibitor of metalloproteinases (TIMP) and stromelysin mRNA simultaneously in synovial tissue. Coexpression of both mRNA species was identified in a subpopulation of intimal lining cells. In some highly inflammatory tissues, virtually all of the lining cells hybridized to both probes. However, in other tissues, expression of the two genes was discordant, with large numbers of TIMPpositive/stromelysin(negative) cells. Similar results were observed with late-passage cultured synoviocytes. Unstimulated cells did not express the stromelysin gene, whereas TIMP was constitutively produced. Addition of interleukin-1 beta (IL-1 beta) or tumor necrosis factor-alpha (TNF-alpha) to cultures induced the former but had little effect on the latter. Double-label experiments clearly showed discordant expression in individual cells. Stromelysin and TIMP genes likely have distinct transcriptional controls that provide precise control over the local environment and matrix turnover.